Application of The Admiralty Method to Process Tidal Data in the Waters of The Nasik Strait - Bangka Belitung - Pasaribu, Roberto Patar; Sewiko, Roni; Arifin, Arifin (Sam Ratulangi University, 2022)
Tides are the rise and fall of sea level caused by the attraction of objects in the sky, especially the moon and sun, to the mass of seawater on earth. Tidal research is useful for providing information about the components and types of tides and predicting tides and for mitigating natural disasters. Tidal measurements were carried out in the Nasik Strait, Bangka Belitung using the Valeport 106 tool. Tidal data was processed using the Admiralty Method. The Admiralty method is a method used to calculate tidal harmonic constants from observations of water levels. With this method, it is possible to know the amplitude and phase difference of the tides, the value of the Formzahl number, and the type of tide. From the results of data processing and analysis, the value of the Formzahl number in the waters of the Nasik Strait is 11,454 and the tidal type is a single daily tidal type that only occurs at one high tide and one low tide in one day.Keywords: tides; tidal types; admiralty method; formzahl numberAbstrakPasang surut adalah naik turunnya muka air laut yang disebabkan oleh gaya tarik benda-benda di langit, terutama bulan dan matahari terhadap massa air laut yang ada di bumi. Penelitian pasang surut bermanfaat untuk memberikan informasi mengenai komponen dan tipe pasang surut sertaÂ memprediksi pasang surut serta untuk mitigasi bencana alam. Pengukuran pasang surut dilakukan di Perairan Selat Nasik, Bangka Belitung dengan menggunakan alat Valeport 106. Data pasang surut diolah dengan menggunakan Metode Admiralty. Metoda Admiralty merupakan metode yang digunakan menghitung konstanta harmonik pasang surut dari pengamatan ketinggian air. Dengan metoda ini dapat diketahuiÂ amplitudo dan beda fase pasang surut, nilai bilangan Formzahl dan tipe pasang surutnya. Dari hasil pengolahan dan analisa data diperoleh nilai bilangan Formzahl di perairan Selat Nasik yaitu 11,454 dan tipe pasang surut adalah tipe pasang surut harian tunggal yang hanya terjadi satu kali pasang dan satu kali surut dalam satu hari.Kata Kunci: pasang surut; tipe pasang surut; metode admiralty;Â bilangan formzahl